Conamomum odorum , a new species of Zingiberaceae from central Vietnam - Truong, Luu Hong; Dang, Tran Huu; Dat, Nguyen Quoc; Trung, Nguyen Tran Quoc; Gioi, Tran (Academia Journal of Biology, 2019)
Conamomum odorum is described as a new species from Khanh Hoa Province, Central Vietnam. It is characterized by sweet smell, striate and narrowly elliptic leaf leaves with short petiole and ligule, ovoid congested inflorescence, pubescent calyx, cream corolla lobes, yellow, obovate and reflexed labellum with median red bands at base and hairy ovary. The new species is illustrated with detailed photographs of key characters and morphologically compared to its closest congeners C. piereanum and C. rubidum. A distribution map of the genus in Vietnam is provided.